Influence of the mastique binder in the bituminous mixtures behaviour - Silva, Hugo Manuel Ribeiro Dias da (2005)
The flexible road pavements are subjected to the repetitive traffic loading, which, among others factors, originate their natural or premature degradation. The bituminous mixtures behaviour must be evaluated using repetitive loading tests that allow the study of their fundamental properties (i.e. fatigue, permanent deformations, and stiffness modulus) when subjected to the loading conditions which occur in the pavement. The behaviour of the bituminous mixtures is strongly influenced by the mastic properties and thus the objective of this work is to study the influence of the mastic characteristics in the bituminous mixtures behaviour. This behaviour was analysed by the evaluation of the complex modulus and fatigue life using repetitive bending at four points and the permanent deformation evaluated using repetitive simple shear tests at constant height (load control). In this work the mastic was defined as the material (filler, fine aggregate and bitumen) which is bonded to the coarse aggregates in a bituminous mixture.